1996
DOI: 10.1007/bf02048544
|View full text |Cite
|
Sign up to set email alerts
|

Elevated triglyceride-rich lipoproteins in diabetes

Abstract: The role of the intestine in cholesterol metabolism in human diabetes is unclear, although abnormalities have been demonstrated in cholesterol synthesis and absorption in diabetic animals. This study examines the relationship between fasting and post-prandial apolipoprotein B-48 in type 2 (non-insulin-dependent) diabetic and non-diabetic subjects. Eight type 2 diabetic patients and ten healthy non-diabetic control subjects were given a high-fat meal (1300 kcal), and the triglyceride-rich lipoprotein fraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…The other postprandial particle is the apo B100-containing VLDL, which is produced by the liver. We and others (11, [13][14][15] have shown very considerable disturbance in both the amount and the size of these particles in diabetes. We have demonstrated in the experimental animal that clearance and synthesis of these particles account for the abnormalities found in diabetes (16,17).…”
mentioning
confidence: 68%
“…The other postprandial particle is the apo B100-containing VLDL, which is produced by the liver. We and others (11, [13][14][15] have shown very considerable disturbance in both the amount and the size of these particles in diabetes. We have demonstrated in the experimental animal that clearance and synthesis of these particles account for the abnormalities found in diabetes (16,17).…”
mentioning
confidence: 68%
“…However, there is evidence to suggest that the intestine constitutively synthesizes smaller TRL particles 48 and maintains a basal level of apoB-48, even in the fasting state. 2 The current thinking is that chylomicron formation involves the formation of small, phospholipidrich, TG-poor primordial particles in the membrane of the smooth endoplasmic reticulum, with subsequent core lipid expansion and particle transfer from the smooth endoplasmic reticulum to the golgi for secretion. 49 We have shown previously that hamster enterocytes have the capacity to secrete small, lipid-poor (HDL size) apoB-48 -containing particles, and that in hamsters made insulin-resistant with fructose or high-fat feeding, there is a marked increase in TRL apoB-48 secretion not only in the fed but also in the fasted state.…”
Section: Table 2 Plasma Lipids and Trl Tg And Apob Concentrations Inmentioning
confidence: 99%
“…1 It is also now well established that insulin-resistant and type 2 diabetic individuals have elevated levels of TG-rich lipoprotein (TRL) particles and remnants, including intestinally derived apolipoprotein B-48 (apoB-48)-containing TRL, in both the fasted and postprandial states. [2][3][4][5][6] The latter is of particular clinical importance because these remnant lipoprotein particles may impair endothelial function and may enter and be retained in the subendothelial space of the vascular wall, thus potentially accelerating the development of atherosclerotic lesions. [7][8][9] Indeed, elevated intestinally derived remnant lipoproteins have been associated with increased cardiovascular disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the isolated lipoproteins were very similar to CM. Diabetes mellitus is a typical disease associated with lipid abnormalities, such as hypertriglyceridemia and low HDL-cholesterol, as well as an increase of remnant lipoproteins 26) . It was shown by the JDCS 27) , a Japanese study, that the incidence of coronary artery disease is higher in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%